Implementasi Tes Kesemaptaan Jasmani melalui Teknologi Computer Vision dan IoT terhadap Pembinaan TNI Polri pada Daerah Magelang - Aisyah, Dinda Nur; Sembiring, Zamalludin (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of physical fitness as a primary requirement in the selection and training process for prospective members of the Indonesian National Armed Forces (TNI) and the National Police (Polri), given that these professions demand optimal physical and mental readiness. The aim of this study is to examine the implementation of physical fitness tests in supporting the training process for TNI and Polri candidates in the Magelang region. A descriptive qualitative approach was used, with data collected through interviews, direct observation, and documentation studies at local physical training institutions. The findings indicate that the implementation of physical fitness tests using computer vision and Internet of Things (IoT) technologies in Magelang has followed standard procedures, including the 12-minute run, push-ups, sit-ups, pull-ups, and shuttle run. However, challenges remain, such as limited training facilities, a shortage of certified trainers, and low participant awareness of maintaining fitness outside of training hours. Continuous training has proven effective in improving participants' physical endurance, discipline, and mental preparedness. The computer vision- and IoT-based system demonstrated a very high correlation with manual results (r > 0.95), confirming its validity as a physical evaluation tool. In conclusion, the implementation of this technology plays a vital role in supporting physical training in the digital era, particularly in shaping character, physical resilience, and mental readiness of future soldiers and police officers. The study recommends improving facilities, increasing the number of certified trainers, and strengthening systematic training programs for more optimal training outcomes.